Abundance and diversity of plant parasitic nematodes associated with vegetable cultivation on various types of organic fertilizers - Siwi Indarti; Taryono Taryono; Chandra Wahyu Purnomo; Ayu Suci Wulandari; Rina Maharani (Society for Indonesian Biodiversity, 2023)
Abstract. Indarti S, Taryono, Purnomo CW, Wulandari AS, Maharani. 2023. Abundance and diversity of plant parasitic nematodes associated with vegetable cultivation on various types of organic fertilizers. Biodiversitas 24: 1010-1016. Planting organic crops is inextricably linked to the presence of Plant-Parasitic Nematodes (PPNs) as a limiting factor. A survey was conducted to determine the abundance and prevalence of PPNs, their correlation with soil chemical properties, and their diversity index in October 2019 at the organic land of the Agrotechnology Innovation Centre, Universitas Gadjah Mada, Kalitirto, Sleman, Special District of Yogyakarta, Indonesia. The organic land was designed as three blocks of different organic fertilizers, including milk sludge fertilizer, cow manure fertilizer, and goat manure fertilizer. The samples were taken by simple randomized sampling method with replications and composited for each treatment in each vegetable plot. Three nematode genera of PPNs were associated with organic vegetable crops in Agrotechnology Innovation Centre, Rotylenchulus sp., Meloidogyne sp., and Helicotylenchus sp. The most common PPNs found was Rotylenchulus sp. with populations of 1388/5 gr roots and 1064/100 mL soil. The other genera, Meloidogynesp. and Helicotylenchus sp. were found with less than 100 nematodes per 5 gr of roots and per 20 gr of soil. C-organic was positively correlated with the Rotylenchulus sp. population. The C/N ratio had a positive effect on the Meloidogyne sp. population, while N-total had a negative effect on the Meloidogyne sp. population. The PPN community diversity index value on the organic land was low (range 0.36-0.37). It indicated that the habitat conditions were relatively homogeneous. It is necessary to carry out integrated management of nematodes to suppress Rotylenchulus sp. population in addition of organic fertilizers on this land.